2017
DOI: 10.3928/01477447-20161229-01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Orthopedic Trauma Surgery Follow-up and Impact of a Routine Callback Program

Abstract: A high rate of patients lost to follow-up is a common problem in orthopedic trauma surgery. This adversely affects the ability to produce accurate clinical outcomes research. The purpose of this project was to (1) evaluate the rate of loss to follow-up at an academic level I trauma center; (2) identify the patient-reported reasons for loss to follow-up; and (3) evaluate the efficacy of a routine patient callback program. All patients who underwent surgery in the orthopedic trauma division of the University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Patients who do not experience any postoperative complications may potentially not be likely to travel long distances and spend time away from work just to confirm their personal perception that their treatment was successful. In support of this, Casp et al [3] reported that patients who reported feeling well did not see the need to attend follow-up visits. They concluded that the lack of follow-up results from a voluntary decision by the patient not to seek further medical care, rather than the failure of logistics or scheduling to provide the patient with adequate care and followup appointments.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Patients who do not experience any postoperative complications may potentially not be likely to travel long distances and spend time away from work just to confirm their personal perception that their treatment was successful. In support of this, Casp et al [3] reported that patients who reported feeling well did not see the need to attend follow-up visits. They concluded that the lack of follow-up results from a voluntary decision by the patient not to seek further medical care, rather than the failure of logistics or scheduling to provide the patient with adequate care and followup appointments.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study reported that 46.3% of all patients who failed to follow up reported 'feeling good' and hence did not feel the need to follow up, subsequently failing to report for scheduled follow-up visits. [3] When these reported factors are combined with long travel distances and poverty, the likelihood of return is further decreased. [3] Lack of follow-up can often lead to skewed results and influence study outcomes and validity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is even more likely that baseline characteristics included in the current analysis explain less variation in LTFU than other, unmeasured variables -variables not reliably available through retrospective record review. For example, smoking, [28][29][30]32,33] substance abuse, [28,29,33,40] feeling well [24,40,41] and a low level of education [17,31,33,40] have all been linked with loss to follow-up in TB-and trauma-related studies. Furthermore, the previously identified role of low income or poverty [28,31] may be particularly important in the current population, most of whom come from a low socioeconomic background, are unable to work for extended periods of time, and may have to weigh the expense of travel to the hospital against competing costs such as food.…”
Section: Researchmentioning
confidence: 99%